Demand and Characteristics of Customers of Reusable Products in Slovenia - Zajko, Katja; Bradač Hojnik, Barbara (Naše gospodarstvo/Our economy, 2019)
The main aim of the paper is to analyse whether a demand for reusable products in Slovenia exists and to identify customers’ characteristics in terms of their gender, age, income, education and employment status. We used survey data to investigate what share of customers in Slovenia are buying and are willing to buy reusable products. Furthermore, we investigate whether there are differences between customers who are buying and who are not buying reusable products with regard to selected demographics (gender, age, income, education and employment status). The findings show that more than half of customers in Slovenia are already buying reusable products. The results of selected characteristics of individuals indicate that there are differences among buyers and non-buyers of reusable products only with regard to gender. The paper contributes to the literature on the demand for reusable products and gives better insights into the characteristics of customers buying reusable products.